PENDIDIKAN DI LAGGER ONDERWIJS MENURUT H.O.S COKROAMINOTO DAN RELEVANSINYA DENGAN KURIKULUM MERDEKA DI MADRASAH IBTIDAIYAH - Rizki Amalia, Rina; Wachid Bambang Suharto, Abdul (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This research is aimed at describing and analyzing educational practices in Lagger onderweijs according to H.O.S Cokroaminoto and their relevance to the independent curriculum at Madrasah Ibtidaiyah. This research uses a qualitative approach with a character study type of research. The data consists of primary data and secondary data collected using documentation techniques using Google Scholar services. The data was then analyzed using content analysis techniques. The results of the research show that H.O.S Cokroaminoto's ideas about education at Lagger onderweijs consist of national character education, organizational education and fun learning. All three have relevance to the learning principles in the independent curriculum at MI, namely involving students to be free, active and creative in learning based on certain topics. National character education also strengthens the identity of the nation's children who have religious character, nationalism, global insight, independence, creativity and critical reasoning which are relevant to the six dimensions of the Pancasila student profile in the independent curriculum. Meanwhile, H.O.S Cokroaminoto's idea of organizational education which teaches its members to reason critically by discussing, giving speeches and journalism is relevant to the learning principles in the independent curriculum which directs students to have literacy skills, critical reasoning and high level thinking or High Order Thinking Skills (HOTS).